2018
DOI: 10.1021/acs.jmedchem.7b01284
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Impact of a Membrane-Anchoring Moiety on the Biological Activities of Bivalent Compounds As Potential Neuroprotectants for Alzheimer’s Disease

et al.

Abstract: Bivalent compounds anchoring in different manners to the membrane were designed and biologically characterized to understand the contribution of the anchor moiety to their biological activity as neuroprotectants for Alzheimer’s disease. Our results established that the anchor moiety is essential and we identified a preference for diosgenin, as evidenced by 17MD. Studies in primary neurons and mouse brain mitochondria also identified 17MD as exhibiting activity on neuritic outgrowth and the state 3 oxidative ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…Oxidative Medicine and Cellular Longevity [27,58]. The results showed a clear structural preference for the introduction of the methylene carbon between diosgenin and curcumin.…”
Section: Pharmacological Activity and Mechanism Of Diosgenin And Its mentioning
confidence: 96%
See 2 more Smart Citations
“…Oxidative Medicine and Cellular Longevity [27,58]. The results showed a clear structural preference for the introduction of the methylene carbon between diosgenin and curcumin.…”
Section: Pharmacological Activity and Mechanism Of Diosgenin And Its mentioning
confidence: 96%
“…Their mechanism of action involves antioxidant activity and inhibitory effects on amyloid-β oligomer formation by directly binding to Aβ [58]. Additionally, DG can act as a membrane-anchoring moiety to improve the access to the cell membrane for the conjugates, suggesting that DG is a novel anchor that can facilitate the multifunctional role of bivalent conjugates for further development as potential therapeutic agents for AD treatment [27]. Recently, Yang et al synthesized a series of multifunctional DG derivatives and evaluated their effect from Aβ-induced damage in PC12 cells and improved learning and memory impairments in Aβ-injected mice.…”
Section: Pharmacological Activity and Mechanism Of Diosgenin And Its mentioning
confidence: 99%
See 1 more Smart Citation
“…13 This is in agreement with our recent studies to show that the spacer composition is a key factor in optimizing protective potency. 28 This also suggests that incorporation of a piperazine moiety into the spacer represents a means to improve potency for future structural modifications. Overall, the increase of spacer length from 21 to 37 atoms did not significantly change the protective potency (Table 1).…”
mentioning
confidence: 99%
“…10 Among the tested bivalent compounds, 21MO shows the most potent protection with an EC 50 of 81.86 nM. When compared to a similar bivalent compound with a spacer length of 21 atoms yet different composition, 11 the protective potency is increased by 23 fold (81.86 vs 1848.66 nM, respectively). This further demonstrated that incorporation of a piperazine ring into the spacer significantly improves potency and spacer composition is important for the molecular design of such bivalent compounds.…”
mentioning
confidence: 99%